Butterflies (Lepidoptera: Papilionoidea) of Georgia (Caucasus): annotated review of regional butterfly fauna with vernacular names index, notes on distribution and phenology - Słowińska,Iwona; Jonko,Krzysztof (PeerJ, 2025)
Background It is well known that butterflies are valuable indicators of environmental quality, given their existence in various habitats. Collecting and regularly updating data on species richness, abundance, and distribution of all butterfly species in the country is crucial for effective monitoring and conservation efforts, which can ultimately help minimise biodiversity losses. Since the last publication of the Georgian butterfly list, there have been numerous reports registering taxonomic revisions, nomenclatural changes or providing several new butterfly “cryptic species” based on genetic research. In the following article, based on a review of various sources of data, including existing literature and new, unpublished data, we present an annotated regional checklist of butterflies of Georgia, a country that is a part of the Caucasus ecoregion representing one of 36 biodiversity “hotspots”. Methods A database with all reported species for Georgia was created by compiling information from critical reviews of all available literature reports, records submitted by contributors of three websites dedicated to butterfly fauna, and data deposited in the Global Biodiversity Information Facility (GBIF) database. Various specialised sources were used to extract vernacular species names (Georgian, Russian and English). Results The updated list of butterflies from Georgia includes 244 species of the superfamily Papilionoidea recorded from almost 600 different locations. Nearly 25% of the 244 species were considered rare and extremely rare, while at the same time being at risk of potential extinction. For each species, we present brief phenological information, distribution in Georgia/Caucasus, occurrence status in each region of the country, thumbnails (ventral and dorsal view), as well as a list of vernacular names in Georgian, Russian and English. Regarding species that are reported in the literature as new, uncertain, or questionable in Georgia, we provide the relevant comments. In comparison to the other republics of Transcaucasia (Armenia, Azerbaijan), we noted a similar number of species. Our studies provide a robust baseline of data for further exploration of the Lepidoptera fauna of Georgia. This foundation should help to fill in the gaps in knowledge regarding regional species distribution, phenology, and habitat requirements.
Keywords: Caucasus; Georgia; Biodiversity; Butterflies; Checklist; Vernacular names; Regional distribution